Japanese Calligraphy in the Digital Era - Merino Estebaranz, Aitana (Mirai. Estudios Japoneses, 2021)
This article analyzes the presence Japanese calligraphy maintains in the modern digital artwork in order to understand its evolution and the continuity of some of its essential concepts in digital art. The expression of time, space and emotions shifts in these creations to an interactive 3D space understandable for the international viewer thanks to the utilization of a contemporary language wrapped in the aesthetics of Japanese traditional culture.
Keywords: shodō; digital calligraphy; Sisyu; teamLab